Transformacije ljudskega kot intertekstualni princip v pesemskem ustvarjanju druge svetovne vojne in refleksije svobode - Golež Kaučič, Marjetka (Studia Historica Slovenica, 2016)
The topic of discussion is the folk poetic tradition or the song of world war two that were created of song in this period. It is the use of folk songs and their transformation that show the typical work of Slovenian creators in a certain period, marked by the depletion of values, existential anguish or the search of new ways of communication, they return to folk tradition in a passive, imitative or active and transformative way. We are interested primarily in the so called intertextual principle that made it possible for the source material to serve as the foundation or that an already known text matrix could be used in a new way. In the analysis of example songs, we also shed light on the concepts, perception and living of freedom as it is reflected in the songs themselves
Keywords: druga svetovna vojna; literarni motivi; slovenska poezija; slovenske ljudske pesmi; svetovna vojna 1939-1945